Penerapan Pencucian Luka Menggunakan Air Rebusan Daun Jambu Biji pada Malodor Luka Diabetes Mellitus di Wilayah Sragen - Yeti Novitasari; Erika Dewi Nooratri (Jurnal Anestesi, 2024)
Data from the Word Health Organization (WHO) shows that the incidence of diabetes mellitus in adults in 2021 is 9.1% in the world. Cases of diabetes mellitus in Indonesia reached a total of 19.47 million with sufferers in Central Java 7.3%. The prevalence of DM in 25 health centers in Sragen Regency was 21,461 people in 2019 and has the potential to experience complications of diabetic ulcers which if left untreated will cause wound tissue regeneration to be disrupted resulting in bacterial infection and an impact on the appearance of odor in the wound. For this reason, it is necessary to make efforts to wash the wound so that the wound remains clean and odorless. One of them is by washing the wound using guava leaf decoction water. To determine the effectiveness of guava leaf decoction to reduce malador in diabetic ulcers. This type of research uses descriptive research methods and by observing 2 respondents with a history of diabetes mellitus and given the implementation of wound washing using guava leaf decoction. Malador and pain scale after the intervention experienced an improved status. There is an effect on wound washing using guava leaf decoction on wounds.